Correlation between Sanitation Facilities and Health Outcomes in Indonesia - Lenindo, Lenindo; Adrison, Vid (Universitas Teuku Umar, 2024)
Poor sanitation is a significant contributor to health problems in developing countries. The improper handling of household waste contaminates soil, surface water, and groundwater, posing health risks to communities through water consumption and exposure. This study utilizes data from the National Socioeconomic Survey (Susenas) conducted by the Indonesian Central Bureau of Statistics (BPS) from 2016 to 2018 to examine the relationship between sanitation facilities and household health quality in Indonesia, analyzing a sample of 883,845 households. Using ordinary least squares (OLS) regression, the findings indicate that households with adequate sanitation facilities generally experience better health outcomes. This study underscores the importance of policy prioritization in establishing communal waste treatment facilities, such as wastewater treatment plants (WWTPs), particularly in densely populated areas. This approach aims to mitigate the adverse health impacts of domestic waste pollution on public health.